Assessing the organizational impacts of information technology. (4th August 2014) - Agarwal, Ritu; Tanniru, Mohan
The ability systematically and objectively to assess both positive and negative impacts of information technology is of crucial concern to organizations. This paper proposes a framework for a holistic assessment of the organizational consequences of information technology. Impact is assessed along the two orthogonal dimensions of breadth (local and global effects) and depth (direct and induced effects) resulting in four possible categories. Objective measures for isolating impact are identified for each category. Three illustrative applications of information technology are used to demonstrate how the framework may be operationalized. Managerial implications and insights suggested by the framework for the utilization of information technology are presented.